WEST AUSTRALIAN DESERT PLANTS: AUSTRALIAN ABORIGINAL MEDICINES WITH ANTICANCER POTENTIAL? - Johns, N.; Kerr, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The semi-arid Australian native plants Scaevola spinescens (Goodeniaceae) and Codonocarpus cotinifolius (Gyrostemonaceae) have been reported as having been used by Western Australian Aboriginal people in combination as a cancer cure (1). Very little phytochemical research is published on either of these species. A monograph in an Aboriginal Pharmacopoeia (2) and brief notes by Collins et al. (3), record the constituents of the leaf volatile oil and biological activity of C. cotinifolius respectively. Anecdotal reports of the medicinal use of these plants by Aboriginal people and the authors interest in Australian native plants, prompted samples of S. spinescens (whole plant) and C. cotinifolius (leaves, stem-wood and root-bark) to be extracted (Soxhlet - methanol). The resulting extracts were fractionated (non-polar to polar solvents) and tested for their anti-tumour activity using the crown gall tumour assay with doxorubicin, a well-known antineoplastic drug, as a positive control. Results (Students t-test, p < 0.05) indicated that a number of fractions possessed > 20% inhibition of tumour formation and are therefore considered worthy of further investigation (4). GC/MS analysis was performed to identify major constituents. Our findings support the anecdotal, traditional medicinal uses of these plants.References:1 Reid, EJ & Betts, TJ 1979, Planta Med., 36, 164-173. 2 Aboriginal Communities of the Northern Territory. 1993, Traditional Aboriginal Medicines in the Northern Territory of Australia. CC of the NT of Australia, Darwin. 3 Collins, DJ, Culvenor, et al. 1990, Plants for Medicines. CSIRO Publications, Melbourne. 4 Ferrigni, NR, Putnam, et al. 1982, J. Nat. Prod., 45(6), 679-686.